2004
DOI: 10.1158/1078-0432.ccr-04-0317
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of Annexin I Alterations in Esophageal Squamous Cell Carcinoma

Abstract: Purpose:The purpose is to characterize alterations of the annexin I gene, its mRNA, and protein expression in esophageal squamous cell carcinoma.Experimental Design: Fifty-six cases of esophageal squamous cell carcinoma were analyzed using four microsatellite markers flanking the annexin I gene (9q11-q21) to identify loss of heterozygosity. In addition, we performed (a) single-strand conformation polymorphism and DNA sequencing along the entire promoter sequence and coding region to identify mutations, (b) rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
56
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 17 publications
4
56
0
Order By: Relevance
“…Loss of annexin A1 has been found to be an early event in oesophageal squamous cell carcinoma, and it may function as a tumour suppressor in the development of this type of tumour (Paweletz et al, 2000). Expression of annexin A1 has also been associated with poorly differentiated oesophageal tumours of higher tumour stage (Hu et al, 2004). Together, these studies suggest that dysregulation of annexin A1 loss is important in oesophageal tumour development and progression.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Loss of annexin A1 has been found to be an early event in oesophageal squamous cell carcinoma, and it may function as a tumour suppressor in the development of this type of tumour (Paweletz et al, 2000). Expression of annexin A1 has also been associated with poorly differentiated oesophageal tumours of higher tumour stage (Hu et al, 2004). Together, these studies suggest that dysregulation of annexin A1 loss is important in oesophageal tumour development and progression.…”
mentioning
confidence: 74%
“…In support of these findings, several studies have implicated individual annexins in tumorigenesis. Annexin A1 has been reported to show altered expression in a variety of different cancers, including oesophageal cancer (Paweletz et al, 2000;Hu et al, 2004;Wang et al, 2006), pancreatic cancer (Bai et al, 2004) and hairy cell leukaemia (Falini et al, 2004). In oesophageal adenocarcinoma, the tumour cell expression of annexin A1 has been associated with poor prognosis (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In esophageal cancers, several published reports confirm that the loss of ANXA1 is an early event in tumorigenesis (Paweletz et al, 2000;Xia et al, 2002;Hu et al, 2004). Western blotting and immunohistochemical analysis showed a drastic decrease or complete loss of ANXA1 levels in esophageal tumors and high-grade dysplasia when compared to the paired normal epithelium, implying that ANXA1 plays a functional role in maintaining the normal status of esophageal epithelium (Paweletz et al, 2000).…”
Section: Introductionmentioning
confidence: 93%
“…Suppression or loss of ANXA1 expression reported in different cancers such as prostate (Kang et al, 2002), breast (Shen et al, 2006), esophageal cancers (Paweletz et al, 2000;Xia et al, 2002;Hu et al, 2004) and B-cell non-Hodgkin's lymphoma (Vishwanatha et al, 2004) attributes tumor suppressive function to ANXA1 in these cancers. Furthermore, ANXA1 overexpression promoted caspase-mediated apoptosis in bronchoalveolar cells (Debret et al, 2003) and macrophages (Solito et al, 2001) and facilitated H 2 O 2 -induced apoptosis in thymocytes (Sakamoto et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Research showed that, if can be in the organization or the blood to the tumor markers for early stage esophageal cancer will help to make the right diagnosis, since it is difficult to get early esophageal cancer histological specimens, looking for serum markers for early diagnosis, staging and pathologic types of distinguish has important significance. In the past ten years, have found some of esophageal cancer markers, such as carcinoembryonic antigen (CEA), serum amyloid A (SAA), calcium phospholipid binding protein I (Annexin I) and glutamine transferase 3 (TGM 3), etc (Hu et al, 2004;Du et al, 2007;Banki et al, 2008;Uemura et al, 2009). It has been proved that some markers is able to assess the clinical treatment effect.…”
Section: Discussionmentioning
confidence: 99%